Pigeon pea-mediated soil microbial shifts improve agroecosystem multifunctionality in long-term maize–palisade grass intercropping - Ahmad Nuruddin Khoiri; Nídia Raquel Costa; Carlos Alexandre Costa Crusciol; Cristiano Magalhães Pariz; Ciniro Costa; Juliano Carlos Calonego; André Michel de Castilhos; Daniel Martins de Souza; Paulo Roberto de Lima Meirelles; Igor Vilela Cru; Luiz Gustavo Moretti; João William Bossolani; et al. (Environmental Microbiome)
Abstract Background Intercropping systems enhance agricultural sustainability by promoting ecosystem multifunctionality (EMF). This study examined the impact of adding pigeon pea (M + PG + PP) into a maize–palisade grass (M + PG) intercropping system under a no-till system (NTS) on soil microbial communities and ecosystem services. After five consecutive growing seasons, bulk soil samples from a soybean-based crop-livestock system were analyzed using metagenomics. Results The inclusion of pigeon pea significantly improved the EMF index, with higher plant productivity and slightly enhanced outcomes in soil health, lamb meat productivity, and climate protection. The M + PG + PP treatment enriched Bradyrhizobium spp., which were positively correlated with soil health, plant productivity, and EMF index. Functional analysis indicated that M + PG + PP treatment enhanced nitrogen metabolism, biofilm formation, and exopolysaccharide (EPS) biosynthesis, improving soil fertility and microbial activity. Similarly, functional analysis of microbial plant growth-promoting traits revealed that the M + PG + PP treatment promoted microbial functions related to nitrogen and iron acquisition, sulfur assimilation, and plant colonization, all essential for plant growth and nutrient cycling. In contrast, the M + PG treatment primarily enhanced pathways related to competitive exclusion and phytohormone production. Conclusions These findings highlight the importance of incorporating legumes such as pigeon pea into intercropping systems to optimize ecosystem services, enhance soil health, and promote long-term agricultural productivity and sustainability.